2017
DOI: 10.1002/2017ja024205
|View full text |Cite
|
Sign up to set email alerts
|

Voyager 1/UVS Lyman α Measurements at the Distant Heliosphere (90–130 AU): Unknown Source of Additional Emission

Abstract: In this work, we present for the first time the Lyman α intensities measured by Voyager 1/UVS in 2003–2014 (at 90–130 AU from the Sun). During this period Voyager 1 measured the Lyman α emission in the outer heliosphere at an almost fixed direction close to the upwind (i.e.“ toward the interstellar flow). The data show an unexpected behavior in 2003–2009: the ratio of observed intensity to the solar Lyman α flux is almost constant. Numerical modeling of these data is performed in the frame of a state‐of‐the‐ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The key result so far is that using the scaling of the Voyager UVS data suggested by Quémerais et al (), there is very good agreement with the results of Hall () and Hall et al () regarding the unexpectedly slow decline in the IPM Lyα brightness seen in the upstream direction. This result strongly suggests the presence of an ~40 R background of Lyα from beyond the heliopause, similar to the 25 R background recently found by Katushkina et al () in their analysis of 90–130 AU Voyager 1 UVS data.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The key result so far is that using the scaling of the Voyager UVS data suggested by Quémerais et al (), there is very good agreement with the results of Hall () and Hall et al () regarding the unexpectedly slow decline in the IPM Lyα brightness seen in the upstream direction. This result strongly suggests the presence of an ~40 R background of Lyα from beyond the heliopause, similar to the 25 R background recently found by Katushkina et al () in their analysis of 90–130 AU Voyager 1 UVS data.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, as originally suggested by Hall (1992) and Hall et al (1993) and more recently explored by Katushkina et al (2017), it appears that a more plausible explanation for the gradual falloff in IPM Lyα brightness viewed in the upwind direction is that the expected 1/r falloff is accompanied by a constant background emission, from beyond the heliopause. While a possible source for this added background is scattered solar Lyα from a "hydrogen wall" just outside the heliopause (Baranov, 1990;Baranov & Malama, 1993;Fayock et al, 2013), the analysis of Voyager 1 UVS data at 90-130 AU by Katushkina et al (2017) strongly suggests that the source is more distant and is not consistent with reflected solar Lyα emissions. Future observations by New Horizons may enable more complete understanding of this background emission.…”
Section: Observationsmentioning
confidence: 57%
See 2 more Smart Citations
“…Since the unresolved-point-sources contribution depends on the spectral sensitivity of a given instrument, the estimations presented in this paper should be considered as specific for the SOHO/SWAN instrument. For other instruments the estimations can be different, but we assess the background is likely to amount to tens of Rayleighs, which is interesting, e.g., in the context of recent studies by Katushkina et al (2017), where an additional emission of ∼25 R was identified as not accounted by models of the Lyman-α glow but obviously present in observations performed for an upwind field of view from the Voyager 1/UVS instrument. Our conjecture is that the unresolved-point-sources background may possibly contribute to the unaccounted emission seen by the UVS instrument.…”
Section: Discussionmentioning
confidence: 99%